2020
DOI: 10.1002/jsfa.10598
|View full text |Cite
|
Sign up to set email alerts
|

Black tea benefits short‐chain fatty acid producers but inhibits genus Lactobacillus in the gut of healthy Sprague–Dawley rats

Abstract: BACKGROUND: The gut microbiota plays important roles in physiological and pathological processes of the host. The effect of black tea on the gut microbiota of healthy individuals remains unclear. RESULTS: Healthy Sprague-Dawley (SD) rats were given black tea for 4 weeks, and cecum content, serum, intestinal, and hepatic samples were collected. The results showed that black tea increased ⊍-diversity and modulated ⊎-diversity of the gut microbiota. Additionally, black tea enriched several short-chain fatty acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For example, the relative abundance of Lactobacillus was higher (13.74%) at the final stage, W4, and it helps in digestion, is beneficial for human and animal intestines, and is being widely used in the biosynthesis of yogurt and sausage (Cavalheiro et al, 2019). Lactobacillus present in black tea is also beneficial for intestinal flora and the health of mice (Arellano et al, 2020;Gao et al, 2020). The share of Saccharopolyspora was 2.85% at the W4 stage, which is an antitumor agent (Liu et al, 2005); therefore, it can be used in food processing to increase the health benefits of dark tea.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relative abundance of Lactobacillus was higher (13.74%) at the final stage, W4, and it helps in digestion, is beneficial for human and animal intestines, and is being widely used in the biosynthesis of yogurt and sausage (Cavalheiro et al, 2019). Lactobacillus present in black tea is also beneficial for intestinal flora and the health of mice (Arellano et al, 2020;Gao et al, 2020). The share of Saccharopolyspora was 2.85% at the W4 stage, which is an antitumor agent (Liu et al, 2005); therefore, it can be used in food processing to increase the health benefits of dark tea.…”
Section: Discussionmentioning
confidence: 99%
“…Many Aspergillus species produce and secrete various enzymes, such as α-amylase, glucoamylase, cellulase, pectinase, xylanase, hemicellulase, and protease, which are applied on an industrial scale to improve the taste of food items by breaking down proteins or lipids and developing unique flavors [33]. Additionally, Aspergillus cristatum is widely used in making crimson soup from dark tea, and lovastatin, a chemical secreted by this genus, is a statin that lowers cholesterol levels [34,35]. Further studies are needed to explore the probiotic properties of individual fungal species and their role in nutrition enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relative abundance of Lactobacillus was higher (13.74%) at final stage W4, which help in digestion, beneficial for human and animal intestine, and is being widely used biosynthesis of yogurt and sausage [32]. Lactobacillus is also beneficial for intestinal flora and health of mice present in black tea [33,34]. The share of www.videleaf.com Saccharopolyspora was 2.85% at W4 stage, which is an antitumor agent [35], therefore, it can be used in food processing to increase health benefits of dark tea.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the importance of gut microbiota metabolites, a large number of studies about these metabolites have been carried out in recent decades and have found out that these metabolites belong to short‐chain fatty acids (SCFAs) (Morrison & Preston, 2016), BAs (Sayin et al, 2013), vitamin K (Karl et al, 2017), branched‐chain amino acids (Yue et al, 2019), tryptophan (Gao, Mu, Farzi, & Zhu, 2020, Gao, Xu, & Yin, 2020), lipopolysaccharide (LPS) (Di Lorenzo, De Castro, Silipo, & Molinaro, 2019), trimethylamine (TMA) (Rath, Heidrich, Pieper, & Vital, 2017), and so on. Based on the origin of these metabolites, gut microbiota metabolites are classified into three types (Postler & Ghosh, 2017).…”
Section: Gut Microbiota and Its Metabolismmentioning
confidence: 99%